Ética Hospitalidad en la Gestión Turística Comunitaria de los Cantones Riobamba y Guamote, Provincia de Chimborazo. - Guambo Manya, Noemi Alexandra (2022)
The present investigation contributes new concepts and approaches in the tourist management of the indigenous communities in the province of Chimborazo, from the vision of the dimension of ethical hospitality. The existence of numerous community organizations, which have decided to assume the tourist service as a means of sustainability, requires researchers, academics and public officials to develop methodologies, tools and instruments in favor of competitiveness in tourist services and meet expectations. of visitors, in addition to measuring the perception of satisfaction. In this investigative work, the field of study is the professional ethical dimension. The absence of evidence, in addition to the ignorance by the actors in the communities, in charge of the service and tourism management, in terms of behavior, projection, attitudes, language referred to professional ethics, negatively influences the performance of tourism management. Then, a knowledge gap is filled, pertinent in the community performance in the attention to tourists. The objective achieved in this research is to demonstrate the impact of the ethical-hospital dimension in community tourism management in the Guamote Canton and San Juan parish, Riobamba canton, Chimborazo province. In addition, the perception of the visiting tourist is characterized, in terms of the ethical-hospital dimension in tourism management; Instruments are provided to determine the degree of perception of ethical hospitality and the feasibility of designing an educational strategy for training and professionalizing tourism management in the indigenous tourism communities of the Guamote and Riobamba cantons, Chimborazo province, is demonstrated. The hypothesis demonstrated is that, by intervening in the perception of the ethical-hospital dimension, tourism management is improved in indigenous tourism communities in the Guamote Canton, San Juan parish, Riobamba canton, Chimborazo province. The practical justification lies in improving community tourism management, from the perspective of the ethical-hospital dimension, interpersonal, inter- organizational community relationships with the tourist visitor.